Promoting Rural Prosperity in the Americas: 2006-2010 Medium-Term Plan - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
This document is product of the Inter-American Institute for Cooperation on Agriculture (IICA), to adapt what it knew of agriculture, rurall territories and cultural diversity. They develop a new Medium term plan for 2006-2010 as a basic management tool. Includes hemisferic mandates, aswise Ministerial Meetings on Agriculture and Rural Life.